Perbankan Konvensional Versus Perbankan Syariah Dalam Realitas Sosiologis - Muhajir, Ahmad; R, Abdurrahman; Gassing, Qadir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Islamic banking, as part of the Islamic financial structure, plays a role in economic development. However, many still consider the Islamic banking system to be similar to the conventional banking system. This perception is based on the additional elements of loans for Islamic banks and deposits for customers of Islamic banks. Upon deeper examination, this view is incorrect because although there are similarities between Islamic and conventional banking, they have fundamental differences. Islamic banking activities are based on Sharia principles. Services in payment transactions between banks and other parties for deposit placement or business financing, among other activities, are based on principles such as mudarabah, musyarakah, murabahah, and ijarah. In contrast, conventional banking provides services in payment transactions with the principle of interest rate determination as the price, for both savings products and loans (credit) given based on a certain interest rate. For other bank services, banks apply fee-based costs.